Ternary composite positive electrode material, preparation method thereof, positive electrode plate, lithium-sulfur battery and electric equipment
By using ternary composite positive electrode materials in lithium-sulfur batteries, including sulfur material core, conductive material and anatase titanium dioxide coating, the problem of limited specific capacity and rate performance of lithium-sulfur batteries is solved, and the improvement of high energy density, rate performance and cycle stability performance is achieved.
Patent Information
- Application Number
- CN202411800699.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-04-25
AI Technical Summary
In actual applications, lithium-sulfur batteries have problems such as limited specific capacity and rate performance, low Coulomb efficiency, rapid capacity attenuation and serious self-discharge. In addition, the volume changes in elemental sulfur during charging and discharging, resulting in mechanical damage to the conductive structure of the electrode sheet.
A ternary composite positive electrode material is provided, including a sulfur material core, a conductive material and anatase titanium dioxide coating layer. The conductive material is doped in the sulfur material core to form a conductive network, and a part of the conductive material extends out of the titanium dioxide coating layer. This material is obtained by thorough mixing in an organic solvent by preparation method, precipitation with ammonia and heating treatment.
This ternary composite positive electrode material can improve the energy density, rate performance and cycle stability of lithium sulfur batteries, inhibit the dissolution diffusion of lithium polysulfide and the volume expansion of sulfur, and enhance the deintercalation lithium capacity and Coulomb efficiency of the material.
Smart Images

Figure CN119890250A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of lithium-sulfur batteries, and in particular to a ternary composite positive electrode material and a preparation method thereof, as well as a positive electrode sheet, a lithium-sulfur battery and an electrical device. Background Art
[0002] Sulfur has a theoretical specific capacity of up to 1675mAh / g, making it an ideal cathode material. When it is assembled into a lithium-sulfur battery with a metallic lithium negative electrode, its theoretical energy density is as high as 2600Wh / kg, which is about ten times that of current commercial lithium-ion batteries. Therefore, lithium-sulfur batteries are regarded as one of the most promising energy storage systems, and sulfur has the advantages of abundant resources, low cost, and green environmental protection, which makes lithium-sulfur batteries have excellent commercial application prospects. However, there are many limitations in its practical application. For example, elemental sulfur and its discharge products (lithium polysulfide) have low electronic and ionic conductivity, which seriously limits the specific capacity and rate performance of lithium-sulfur batteries; the lithium polysulfide produced during the discharge process will dissolve into the electrolyte and easily form a "shuttle effect" to the negative electrode, resulting in low coulomb efficiency, rapid capacity decay and severe self-discharge of the battery; and the severe volume change of elemental sulfur during the charge and discharge process can easily cause mechanical damage to the conductive structure of the pole piece. Summary of the invention
[0003] In view of this, the purpose of the present application is to provide a ternary composite positive electrode material and a preparation method thereof, so that the ternary composite positive electrode material can ensure that the lithium-sulfur battery has high energy density, rate performance and cycle stability at the same time;
[0004] Another object of the present application is to provide a positive electrode sheet, a lithium-sulfur ion battery and an electrical device based on the above-mentioned ternary composite positive electrode material.
[0005] In order to solve the above technical problems / achieve the above purposes or at least partially solve the above technical problems / achieve the above purposes, as a first aspect of the present application, a ternary composite positive electrode material is provided, comprising a sulfur material core, a conductive material and an anatase titanium dioxide coating layer, wherein the anatase titanium dioxide coating layer coats the sulfur material core, the conductive material is doped into the sulfur material core to form a conductive network and part of the conductive material extends out of the titanium dioxide coating layer.
[0006] Optionally, the mass ratio of the sulfur material core, the conductive material and the anatase titanium dioxide coating layer is (80-90):(1-9):(1-5).
[0007] Further optionally, the conductive material includes one or more of conductive carbon black, carbon nanotubes, graphene, and conductive carbon cloth.
[0008] As a second aspect of the present application, a method for preparing the ternary composite positive electrode material is provided, comprising:
[0009] The sulfur material and the conductive material are fully mixed in an organic solvent, and then fully mixed with a titanium source material to obtain a precursor solution;
[0010] Ammonia water is added to the precursor solution to generate a precipitate, and the precipitate is separated to obtain an amorphous titanium dioxide / sulfur / conductive material ternary composite material;
[0011] The amorphous titanium dioxide / sulfur / conductive material ternary composite material is heated to obtain anatase titanium dioxide / sulfur / conductive material ternary composite positive electrode material.
[0012] Optionally, the titanium source material includes tetrabutyl titanate. Further optionally, the mass ratio of the sulfur material: conductive material: tetrabutyl titanate: ammonia water is (80-90): (1-9): (5-15): (1.5-4.5).
[0013] Optionally, the temperature of the heating treatment is 400-500°C.
[0014] As a third aspect of the present application, a positive electrode plate is provided, comprising a current collector and a positive electrode active material coated on a surface of the current collector, wherein the positive electrode active material comprises the ternary composite positive electrode material described in the present application.
[0015] As a fourth aspect of the present application, a lithium-sulfur battery is provided, comprising a negative electrode plate, the positive electrode plate described in the present application, a separator and an electrolyte.
[0016] As a fifth aspect of the present application, an electrical device is provided, comprising the lithium-sulfur battery described in the present application, wherein the lithium-sulfur battery provides electrical energy for the electrical device.
[0017] The sulfur material used in the present application has a high lithium insertion and extraction capacity, which can ensure that the positive electrode material and the lithium-sulfur battery have a high mass energy density; the anatase titanium dioxide material used as a coating layer can effectively inhibit the volume change of sulfur during the charging and discharging process, and the titanium dioxide material has a strong adsorption capacity for polysulfides, which can effectively inhibit the dissolution and diffusion of polysulfides, thereby improving the cyclic stability of the material. In addition, anatase titanium dioxide material has excellent cycle stability, excellent rate performance, and good lithium deintercalation capacity. As a coating layer of a ternary positive electrode material, it can improve the rate performance of the material and increase the lithium deintercalation capacity of the material. The coating layer can isolate the sulfur material from contact with the outside air and water, and avoid the sulfur material from producing toxic and harmful gases during the battery manufacturing process, so that the lithium-sulfur battery with the ternary material conforms to the existing production process of lithium-ion batteries and has the advantage of mass production. The conductive material used has a large specific surface area and excellent conductive properties. It can not only be doped in the sulfur particles to form a conductive network, but also part of the conductive material extends out of the titanium dioxide coating layer, which can directly introduce electrons into the interior. This structure can effectively inhibit the dissolution and diffusion of lithium polysulfide and alleviate the volume expansion of sulfur, thereby improving the rate performance and cycle stability of the ternary composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application.
[0019] Figure 1 The structure diagram of the anatase titanium dioxide / sulfur / conductive material ternary composite positive electrode material of the present application is shown;
[0020] Figure 2 Shown is a comparison chart of 100-cycle gram capacity of different embodiments and comparative examples;
[0021] Figure 3 Shown is a comparison chart of rate performance of different embodiments and comparative examples. DETAILED DESCRIPTION
[0022] The present application discloses a ternary composite positive electrode material and a preparation method thereof, as well as a positive electrode sheet, a lithium-sulfur battery and an electrical device. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all deemed to be included in this application. The method described in this application has been described through a preferred embodiment, and relevant personnel can obviously modify or appropriately change and combine the preparation method described in this article without departing from the content, spirit and scope of this application to realize and apply the technology of this application. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0023] It should be noted that, in this article, if relational terms such as "first" and "second", "step 1" and "step 2", and "(1)" and "(2)" appear, they are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "comprise", "include" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the presence of other identical elements in the process, method, article or equipment including the elements. At the same time, the embodiments in this application and the features in the embodiments may be combined with each other without conflict.
[0024] Titanium dioxide materials can form O-Ti-S bonds with lithium polysulfide, so they have strong adsorption capacity for polysulfide, thereby inhibiting its dissolution and diffusion. Titanium dioxide materials have good rate performance and excellent cycle stability. As a coating layer for sulfur materials, they can improve the rate and cycle performance of materials and effectively inhibit the volume change of sulfur materials. Conductive materials such as single-walled carbon nanotubes have a large specific surface area and a wrinkled surface, which can be coated on the outside of sulfur particles to form a conductive network, which can not only inhibit the dissolution and diffusion of lithium polysulfide, but also alleviate the volume expansion of sulfur during the charging and discharging process.
[0025] Therefore, in the first aspect of the present application, a ternary composite positive electrode material is provided, comprising a sulfur material core, a conductive material and an anatase titanium dioxide coating layer, wherein the anatase titanium dioxide coating layer covers the sulfur material core, and the conductive material is doped in the sulfur material core to form a conductive network and part of the conductive material extends out of the titanium dioxide coating layer. Wherein, the conductive material comprises one or more of carbon nanotubes, graphene, and conductive carbon cloth, and these conductive materials are relatively large in size and cannot be completely coated by the titanium dioxide coating layer, so that part of the conductive material can extend out of the coating layer; the carbon nanotubes include single-walled carbon nanotubes and multi-walled carbon nanotubes, and the graphene includes single-layer graphene and multi-layer graphene.
[0026] In certain embodiments of the present application, the conductive material in the ternary composite positive electrode material is carbon nanotubes, and its structural schematic diagram is shown in Figure 1 In some other embodiments of the present application, the carbon nanotubes are selected from single-walled carbon nanotubes, such as single-walled carbon nanotubes with a tube diameter of 1-2 nm and a tube length of 1-5 μm.
[0027] In certain embodiments of the present application, the sulfur material is sulfur particles with a particle size of micrometers, and further, the sulfur material is sulfur particles with a particle size of 2-10 μm.
[0028] In certain embodiments of the present application, the mass ratio of the sulfur material core, the conductive material and the anatase titanium dioxide coating layer is (80-90): (1-9): (1-5). In other embodiments of the present application, the mass ratio of the sulfur material core, the conductive material and the anatase titanium dioxide coating layer is (80-90): (1-9): (1.17-3.52), for example, 85:5:2.34, 89:1:2.34, 81:9:2.34, 90:5:1.17, 80:5:3.52, etc.
[0029] In a second aspect of the present application, a method for preparing the ternary composite positive electrode material is provided, comprising:
[0030] The sulfur material and the conductive material are fully mixed in an organic solvent, and then fully mixed with a titanium source material to obtain a precursor solution;
[0031] Ammonia water is added to the precursor solution to generate a precipitate, and the precipitate is separated to obtain an amorphous titanium dioxide / sulfur / conductive material ternary composite material;
[0032] The amorphous titanium dioxide / sulfur / conductive material ternary composite material is heated to obtain anatase titanium dioxide / sulfur / conductive material ternary composite positive electrode material.
[0033] Among them, adding ammonia water to react decomposes into ammonia gas and water. Water is used for the hydrolysis reaction of the titanium source material. Compared with other similar substances, ammonia water reacts more slowly, which helps the titanium source material to slowly hydrolyze on the surface of the sulfur particle material to form a titanium dioxide coating layer, avoiding excessive reaction and causing uneven titanium dioxide coating.
[0034] In certain embodiments of the present application, the method of sufficient mixing includes but is not limited to ultrasound, ball milling, stirring, etc. In other embodiments of the present application, the sulfur material is first mixed with an organic solvent and ball milled to obtain a sulfur particle slurry with a particle size of 2-10 μm, and then ultrasonically dispersed with a conductive material to obtain a mixed slurry, and then a solution of a titanium source material and an organic solvent is added and stirred to obtain a precursor solution. In other embodiments of the present application, the mass ratio of the sulfur material to the organic solvent can be referenced to 85:1000, and the mass ratio of the titanium source material to anhydrous ethanol can be referenced to 10:10, and the organic solvent includes anhydrous ethanol.
[0035] In some embodiments of the present application, the titanium source material includes tetrabutyl titanate. In some other embodiments of the present application, the mass ratio of the sulfur material: conductive material: tetrabutyl titanate: ammonia water is (80-90): (1-9): (5-15): (1.5-4.5), such as 85: 5: 10: 3, 89: 1: 10: 3, 81: 9: 10: 3, 90: 5: 5: 3, 80: 5: 15: 3, etc.
[0036] In some embodiments of the present application, the temperature of the heat treatment is 400-500° C., such as 400° C., 410° C., 420° C., 430° C., 440° C., 450° C., 460° C., 470° C., 480° C., 490° C. or 500° C. In some other embodiments of the present application, the heating rate is 1-15° C. / min, such as 5° C. / min, 10° C. / min, etc.
[0037] In a third aspect of the present application, a positive electrode plate is provided, comprising a current collector and a positive electrode active material coated on a surface of the current collector, wherein the positive electrode active material comprises the ternary composite positive electrode material described in the present application.
[0038] In certain embodiments of the present application, the positive electrode active material further includes a binder and a conductive agent, and the mass ratio of the three is ternary composite material: binder: conductive agent can be selected as 8-9:0.5-1:0.5-1. The conductive agent includes at least one of conductive carbon black, acetylene black, single-walled carbon nanotubes, multi-walled carbon nanotubes, Ketjen black, or other conductive agents known in the art. The binder includes one or more of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-co-hexafluoropropylene (PVDF-HFP), polymethyl methacrylate (PMMA), polyacrylonitrile (PAN), and poly-m-phenylene isophthalamide (PMIA). In certain embodiments of the present application, the current collector includes a metal foil, such as aluminum foil, copper foil, etc. The ternary composite material, binder, conductive agent and solvent constitute a positive electrode slurry, which is coated on the surface of the current collector, and then the solvent is dried and volatilized to obtain the positive electrode sheet. The solvent can be selected from N-methyl-2-pyrrolidone (NMP), and other solvents known in the art can also be selected.
[0039] In a fourth aspect of the present application, a lithium-sulfur battery is provided, comprising a negative electrode plate, a positive electrode plate as described in the present application, a separator and an electrolyte. The lithium-sulfur battery may include various types of batteries such as soft packs, cylinders or square shells; in certain embodiments of the present application, the present application is assembled into a button battery for corresponding performance testing and evaluation, and the negative electrode plate is a lithium plate.
[0040] In certain embodiments of the present application, the button battery includes a 2025 type button battery, and the specific assembly method is as follows: battery positive electrode shell / positive electrode sheet / diaphragm / lithium sheet / gasket / battery negative electrode shell according to the button battery preparation method from bottom to top: battery positive electrode shell / positive electrode sheet / diaphragm / lithium sheet / gasket / battery negative electrode shell
[0041] In certain embodiments of the present application, the electrolyte can be a conventional lithium-ion battery electrolyte, usually lithium hexafluorophosphate (LiPF6) or lithium bis(trifluoromethylsulfonyl)imide (LTFSI) electrolyte, generally including LiPF6 or LTFSI, and an organic solvent, such as 1 mol / L LiPF6 / EC-DMC electrolyte.
[0042] In a fifth aspect of the present application, an electric device is provided, comprising the lithium-sulfur battery described in the present application, wherein the lithium-sulfur battery provides electric energy for the electric device. The electric device may be various devices or equipment driven by the lithium-ion battery, including but not limited to electric vehicles, electric vehicles, self-balancing vehicles, flatbed vehicles, aircraft, lighting equipment, household appliances, etc.
[0043] In each group of comparative experiments provided in this application, unless otherwise specified, other experimental conditions, materials, etc. are kept consistent except for the differences indicated in each group, so as to provide comparability. The experimental materials and reagents used in the examples can be obtained from commercial channels unless otherwise specified.
[0044] The following is a further description of a ternary composite positive electrode material and a preparation method thereof, as well as a positive electrode sheet, a lithium-sulfur battery and an electrical device provided in the present application.
[0045] Embodiment 1:
[0046] (1) Preparation of ternary composite materials
[0047] Using 1000 g of AR grade analytical pure anhydrous ethanol as a solvent, 85 g of AR grade analytical pure sulfur powder was micron-milled by mechanical ball milling to obtain slurry A, wherein the particle size of the sulfur particles was 2-10 μm, and the mass ratio of sulfur powder to anhydrous ethanol was 85:1000.
[0048] 5 g of single-walled carbon nanotube material was added to the above slurry A, and after ultrasonic dispersion for 2 hours, it was stirred at 600 rpm / min for 1 hour to obtain a uniformly mixed slurry B. The diameter of the single-walled carbon nanotube material was 1-2 nm, and the length was 1-5 μm. The mass ratio of sulfur powder to single-walled carbon nanotube material was 85:5.
[0049] 10 g of tetrabutyl titanate (TBT) was dissolved in 10 g of anhydrous ethanol and stirred at 600 rpm / min for 10 min to form a solution C. The mass ratio of tetrabutyl titanate to anhydrous ethanol was 10:10.
[0050] Solution C was slowly added to slurry B and stirred at 600 rpm / min for 30 min to form precursor solution D.
[0051] At a stirring speed of 600rpm / min, 3g of concentrated ammonia water was slowly dripped into the precursor solution D and stirred for 2h. The precipitate was separated by high-speed centrifugation and dried at high temperature to obtain an amorphous titanium dioxide / sulfur / single-walled carbon nanotube material ternary composite material. The above product was placed in a vacuum environment and heated at 450℃ for 2h at a heating rate of 10℃ / min to finally obtain anatase titanium dioxide / sulfur / single-walled carbon nanotube ternary composite cathode material.
[0052] The mass ratio of sulfur powder is 80-90%, the mass ratio of single-walled carbon nanotube material is 1-9%, the mass ratio of tetrabutyl titanate is 5-15%, and the mass ratio of sulfur powder, single-walled carbon nanotube and tetrabutyl titanate is 100% in total.
[0053] In this embodiment, the mass ratio of sulfur powder: single-walled carbon nanotubes: tetrabutyl titanate: concentrated ammonia water: anhydrous ethanol (total mass) is 85:5:10:3:1010.
[0054] (2) Preparation of positive electrode sheet and battery
[0055] Under the condition of controlling the ambient temperature to 20 degrees Celsius and -60 degrees Celsius dew point, first weigh 25g PVDF-HFP and add it to 1L NMP and stir for 3 hours to obtain a colorless and transparent solution, then add 200g of anatase titanium dioxide / sulfur / single-walled carbon nanotube ternary composite positive electrode material and 25g of conductive carbon black, stir quickly for 4 hours to obtain a uniformly mixed black glue, measure the viscosity with a viscometer to ensure that the viscosity is around 7000-10000cps, the fineness is below 30, and sieve with a 160-mesh double-layer filter. Finally, the mass ratio of active material: binder: conductive agent is 8:1:1;
[0056] The prepared positive electrode slurry is evenly coated on the aluminum foil current collector, dried in an oven at 40-80°C, and then rolled to obtain the positive electrode of the battery. Then, it is placed in a vacuum oven at 60°C for 48 hours to remove moisture and solvent and stored in a vacuum for later use.
[0057] The aluminum foil current collector may be an aluminum foil or a carbon-coated aluminum foil with a thickness of 4-20 μm, wherein the aluminum foil of 12 μm is the best choice;
[0058] Under the condition of controlling the ambient temperature to 20 degrees Celsius and the dew point to -60 degrees Celsius, the prepared positive electrode sheet having the anatase titanium dioxide / sulfur / single-walled carbon nanotube ternary composite positive electrode material was punched into a positive electrode sheet having a diameter of 12 mm.
[0059] A 2025 type button cell was prepared, wherein the button cell consisted of a lithium sheet and the positive electrode sheet prepared above. Under the condition of controlling the ambient temperature to 20 degrees Celsius and the dew point to -60 degrees Celsius, the specific assembly method was as follows: battery positive electrode shell / above prepared electrode sheet / diaphragm / lithium sheet / gasket / battery negative electrode shell from bottom to top according to the preparation method of the button cell. The prepared lithium-sulfur battery with anatase titanium dioxide / sulfur / single-walled carbon nanotube ternary composite positive electrode material was used for corresponding performance testing and evaluation. The electrolyte used was a common 1 mol / L LiPF6 / EC-DMC electrolyte.
[0060] Embodiment 2:
[0061] The difference between Example 2 and Example 1 is that the mass ratio of sulfur powder: single-walled carbon nanotubes: tetrabutyl titanate: concentrated ammonia water: anhydrous ethanol (total mass) is 89:1:10:3:1010. The remaining steps are carried out according to Example 1, and finally a lithium-ion battery electrode sheet and its corresponding 2025-type button battery are obtained.
[0062] Embodiment 3:
[0063] The difference between Example 3 and Example 1 is that the mass ratio of sulfur powder: single-walled carbon nanotubes: tetrabutyl titanate: concentrated ammonia water: anhydrous ethanol (total mass) is 81:9:10:3:1010, and the remaining steps are carried out according to Example 1 to finally obtain a lithium-ion battery electrode sheet and its corresponding 2025 button battery.
[0064] Embodiment 4:
[0065] The difference between Example 4 and Example 1 is that the mass ratio of sulfur powder: single-walled carbon nanotubes: tetrabutyl titanate: concentrated ammonia water: anhydrous ethanol (total mass) is 90:5:5:3:1010, and the remaining steps are carried out according to Example 1 to finally obtain a lithium-ion battery electrode sheet and its corresponding 2025 button battery.
[0066] Embodiment 5:
[0067] The difference between Example 5 and Example 1 is that the mass ratio of sulfur powder: single-walled carbon nanotubes: tetrabutyl titanate: concentrated ammonia water: anhydrous ethanol (total mass) is 80:5:15:3:1010, and the remaining steps are carried out according to Example 1 to finally obtain a lithium-ion battery electrode plate and its corresponding 2025 button battery.
[0068] Comparative Example 1:
[0069] The difference between Comparative Example 1 and Example 1 is that the mass ratio of sulfur powder: single-walled carbon nanotubes: tetrabutyl titanate: concentrated ammonia water: anhydrous ethanol (total mass) is 100:0:0:3:1010, and the remaining steps are carried out according to Example 1 to finally obtain a lithium-ion battery electrode sheet and its corresponding 2025 button battery.
[0070] Comparative Example 2:
[0071] The difference between Comparative Example 2 and Example 1 is that the mass ratio of sulfur powder: single-walled carbon nanotubes: tetrabutyl titanate: concentrated ammonia water: anhydrous ethanol (total mass) is 95:5:0:3:1010, and the remaining steps are carried out according to Example 1 to finally obtain a lithium-ion battery electrode sheet and its corresponding 2025 button battery.
[0072] Comparative Example 3:
[0073] The difference between Comparative Example 3 and Example 1 is that the mass ratio of sulfur powder: single-walled carbon nanotubes: tetrabutyl titanate: concentrated ammonia water: anhydrous ethanol (total mass) is 90:0:10:3:1010, and the remaining steps are carried out according to Example 1 to finally obtain a lithium-ion battery electrode sheet and its corresponding 2025 button battery.
[0074] Experimental example:
[0075] The initial discharge capacity test, the discharge capacity test after 100 cycles, and the discharge capacity test at the discharge rate are all tested using the Blue Power battery testing system.
[0076] (1) Initial discharge capacity test
[0077] First discharge capacity test: At room temperature, the material was discharged at a constant current of 0.1C to 1.7V, left for 10 minutes, and then charged at a constant current of 0.1C to 2.8V. The first discharge capacity of the material was obtained by testing. The first discharge capacities of the embodiments and comparative examples are shown in Table 1.
[0078] Table 1 First discharge capacity of different embodiments and comparative examples
[0079]
[0080] It can be seen from Table 1 that the first discharge capacity of each embodiment of the present application is at a relatively high level; in the comparative examples, although comparative examples 1 and 2 also reach a first discharge capacity of more than 950 mAh / g, the subsequent cycle performance and rate performance are poor, and a single first discharge capacity cannot achieve the expected purpose; the first discharge capacity of comparative example 3 is the lowest among all tests, and the subsequent rate performance and cycle performance are also poor.
[0081] (2) 100-cycle capacity test
[0082] Discharge capacity test of 100 cycles at 0.1C current density: At room temperature, discharge at 0.1C current to 1.7V, leave for 10 minutes, charge at 0.1C current to 2.8V, leave for 10 minutes, and cycle for 100 cycles. The cyclic discharge capacity of the material is obtained by testing; the 100-cycle cycle test discharge capacity curve is shown in Figure 2 ;
[0083] according to Figure 2 It can be clearly seen that after 100 cycles, the discharge capacities of Examples 1 to 5 (Examples 1 to 5 in the figures) are significantly higher than those of Comparative Examples 1 to 3, showing excellent cycle performance.
[0084] (3) Rate performance test
[0085] Discharge capacity test at different discharge rates: At room temperature, discharge at a constant current of 0.1C to 1.7V, leave for 10 minutes, charge at a constant current of 0.1C to 2.8V, leave for 10 minutes, and cycle at this current density for 10 weeks; subsequently, rate tests were performed at current densities of 0.2C, 0.5C, 1C, and 0.1C, and each rate was cycled for 10 weeks. The discharge capacity of the material at different discharge rates was obtained; the discharge capacity at different discharge rates is shown in Table 1. Figure 3 ;
[0086] Figure 3 The results show that the embodiment contains more titanium dioxide material, which makes it have better rate performance and cycle stability. Compared with Examples 1-5, Comparative Examples 1-3 have higher sulfur content and relatively higher initial capacity, but no titanium dioxide coating layer, resulting in poor rate performance and cycle stability, and fast capacity decay.
[0087] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A ternary composite positive electrode material, characterized in that: It comprises a sulfur material core, a conductive material and an anatase titanium dioxide coating layer, wherein the anatase titanium dioxide coating layer covers the sulfur material core, the conductive material is doped in the sulfur material core to form a conductive network and part of the conductive material extends out of the titanium dioxide coating layer.
2. The ternary composite cathode material according to claim 1, characterized in that: The mass ratio of the sulfur material core, the conductive material and the anatase titanium dioxide coating layer is (80-90): (1-9): (1-5).
3. The ternary composite cathode material according to claim 1 or 2, characterized in that: The conductive material includes one or more of carbon nanotubes, graphene, and conductive carbon cloth.
4. The method for preparing the ternary composite positive electrode material according to claim 1, characterized in that: include: The sulfur material and the conductive material are fully mixed in an organic solvent, and then fully mixed with a titanium source material to obtain a precursor solution; Ammonia water is added to the precursor solution to generate a precipitate, and the precipitate is separated to obtain an amorphous titanium dioxide / sulfur / conductive material ternary composite material; The amorphous titanium dioxide / sulfur / conductive material ternary composite material is heated to obtain anatase titanium dioxide / sulfur / conductive material ternary composite positive electrode material.
5. The preparation method according to claim 4, characterized in that: The titanium source material includes tetrabutyl titanate.
6. The preparation method according to claim 5, characterized in that: The mass ratio of the sulfur material: conductive material: tetrabutyl titanate: ammonia water is (80-90):(1-9):(5-15):(1.5-4.5).
7. The preparation method according to claim 4, characterized in that: The temperature of the heating treatment is 400-500°C.
8. A positive electrode sheet, characterized in that: It comprises a current collector and a positive electrode active material coated on the surface of the current collector, wherein the positive electrode active material comprises the ternary composite positive electrode material according to any one of claims 1 to 3.
9. A lithium-sulfur battery, characterized in that: It comprises a negative electrode sheet, the positive electrode sheet as claimed in claim 8, a separator and an electrolyte.
10. An electrical device, characterized in that: It includes the lithium-sulfur battery as described in claim 9, and the lithium-sulfur battery provides electrical energy for the electrical equipment.